2021
DOI: 10.1186/s42408-021-00106-3
|View full text |Cite
|
Sign up to set email alerts
|

Frequent burning in chir pine forests, Uttarakhand, India

Abstract: Background Subtropical coniferous forests of the lesser Himalaya provide critical ecosystem services but fire regimes have received limited scientific attention. We reconstructed fire regimes using tree-ring methods in a chir pine (Pinus roxburghii Sarg.) forest of Uttarakhand, India. We cross-dated tree-ring samples with fire scars from 36 trees at three sites near rural villages between 1535 and 1848 m elevation. Results Fires were highly frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…With the onset of the monsoon, the biomass becomes too wet to burn and the fire season ends. Consequently, forest fires are strictly limited to the dry season (November -March) across the region (Troup 1921;Bahuguna and Upadhyay, 2002;Dorji, 2006;Matin et al, 2017;Fulé et al, 2021). Our fire scar dataset confirmed this pattern for our study site, with 100 % of fire scars occurring in the dry season.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…With the onset of the monsoon, the biomass becomes too wet to burn and the fire season ends. Consequently, forest fires are strictly limited to the dry season (November -March) across the region (Troup 1921;Bahuguna and Upadhyay, 2002;Dorji, 2006;Matin et al, 2017;Fulé et al, 2021). Our fire scar dataset confirmed this pattern for our study site, with 100 % of fire scars occurring in the dry season.…”
Section: Discussionsupporting
confidence: 80%
“…We assessed fire-climate association using SEA analysis. We created fire-event files listing: 1) all fire dates; and, 2) those that scarred at least 25% of the sampled trees that recorded fires (Fulé et al 2021). To determine if there was a relationship between fire occurrence and climate, we analyzed climatic conditions in the year of the fire and the three years that preceded the fire.…”
Section: Data Sets and Analytical Methodsmentioning
confidence: 99%
“…Studies generally have shown that fire induces the growth of grasses in pine forests and that is the main reason of fire ignition by farmers (Fulé et al 2021 ). There is a scarcity of fodder for livestock, which has been an integral part of Uttarakhand’s subsistence farming since the time immemorial (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Fire has promoted the regional domination of chir pine at the expense of broadleaf oak forests (Singh and Singh 1992 ; Semwal and Mehta 1996 ), and the ban on tree cutting above 1000 m elevation since 1981 further favoured chir pine, as branches of oak continued to be cut for fodder and firewood (Thadani 1999 ), while chir pine trees were generally saved. However, resin tapping and fire combine to cause mortality of chir pine trees (Fulé et al 2021 ). One of the major purposes to ignite forest fires is to increase the availability and quality of grasses for feeding domestic animals (Brandis 1897 ; Goldammer 1993 ; Schmerbeck and Seeland 2007 ; Kohli 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…Various studies on the endangered species on genome scale in various reserved forests and zoonotic sanctuaries are done over tigers, elephants, plant browning and early drying, edge effects on diversified vegetation. Changes in massive fires are encountered by the Indian forest and forms fire prone ecosystems are regular and age old issue in forests in hills of Western Ghats, Eastern Ghats, hills of Himalaya's, forests in north east region (NER) states, Nilgiri and Similipal forests [18][19][20][21].…”
Section: Review Of Literaturementioning
confidence: 99%